2022
DOI: 10.3389/fimmu.2021.799171
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Role of CDK4/6 and Potential Mechanism Exploration in Ovarian Cancer

Abstract: BackgroundOvarian cancer (OC) is one of the most lethal gynecologic cancers. Growing evidence has proven that CDK4/6 plays a key role in tumor immunity and the prognosis of many cancers. However, the expression and function of CDK4/6 in OC remain unclear. Therefore, we aimed to explore the influence of CDK4/6 in OC, especially on immunity.MethodsWe analyzed CDK4/6 expression and prognosis using The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO) and Genotype Tissue Expression (GTEx) data. Subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…At present, although the research on gastric cancer has achieved great success, the molecular mechanism of gastric cancer is still not fully understood, and the effective treatment of gastric cancer is still a hot issue [ 2 , 3 ]. Abnormal expression of CDK6 affects the initiation and progression of various malignant tumors [ 4 ]. One of the hallmarks of cancer is cell cycle disorder that leads to abnormal cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…At present, although the research on gastric cancer has achieved great success, the molecular mechanism of gastric cancer is still not fully understood, and the effective treatment of gastric cancer is still a hot issue [ 2 , 3 ]. Abnormal expression of CDK6 affects the initiation and progression of various malignant tumors [ 4 ]. One of the hallmarks of cancer is cell cycle disorder that leads to abnormal cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…AC020907.2 is positively related to overall survival in glioma [ 34 ]. Correlation analysis between AC026461.1 and has-miR-330-5p has been found in ovarian cancer [ 35 ]. HOXC10 is implicated in luminal breast cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown up-regulation of CDK4/6 and pRb levels in HER2 + breast cancer samples [334]. In ovarian cancer samples, up-regulation of CDK6 has been associated with shorted OS and immunosuppressive state [319]. Moreover, in this type of cancer, up-regulation of a functional counterpart of CDK4/6, i.e.…”
Section: Investigations In Clinical Samplesmentioning
confidence: 96%